Voltage-dependent extended shortwave infrared (e-SWIR) photodetection-band tuning utilizing the Moss–Burstein effect. (2nd February 2023) - Xiang, Boyang; Gu, Guiru; Ramaswamyd, Nagarajan; Drew, Christopher; Lu, Xuejun
Abstract: Extended shortwave infrared (e-SWIR) photodetectors and imaging focal plane arrays covering the wavelength beyond the conventional In0.53 Ga0.47 As cutoff wavelength of 1.65 micrometers ( µ m) can find numerous applications in infrared sensing and imaging. This paper reports voltage-tunable e-SWIR photodetectors based on the conventional gallium antimonide (GaSb) n – i – p and p – i – n homojunctions on GaSb substrates, which offer bias-dependent photodetection band tuning with a simple structure and high material crystal quality due to the perfect lattice matching on the substrates. Detection bands between the cutoff wavelengths of 1.7 µ m and 1.9 µ m can be tuned with a low reverse bias voltage of <0.1 volts (V). The mechanism of the voltage-dependent band-tuning was analyzed and attributed to the Moss–Burstein effect, which changes the electron and hole filling factors under different reverse bias voltages. This analysis agreed with the experimental data. The Moss–Burstein effect-induced voltage-dependent band-tuning mechanism can provide useful guidance for the designs of e-SWIR photodetectors.